(untitled) (Brazilian Journal of Oceanography, 2007)
The objective of this study was to quantify the zooplankton biomass transport between the Santa Cruz Channel (SCC) at Catuama north inlet and the adjacent shelf located in Itamaracá estuarine ecosystem, Pernambuco State, Northeastern Brazil. Sampling was carried out in August 2001 at spring and neap tides at three stations every 3-hour interval. Collections were made in three depths with a plankton pump coupled to a 300 µm mesh size net. Current data were obtained with an ADCP (Acoustic Doppler Current Profiler). In laboratory, samples were filtered for wet weigh determination. High biomass variation was recorded, with highest values at nocturnal flood and ebb during spring tide. The average instantaneous biomass transport was 139.48 ± 72.58 mg.m-2s-1, during spring tide and 36.63 ± 27.66 mg.m-2s-1, during neap tide. No significant difference was registered between importation and exportation flows (p >; 0.05), showing that the estuary both exports and imports high biomass during the rainy season. It can be concluded that the outwelling at SCC is high, however, differently from other places, importation is also high, probably due to the presence of reefs and patches of seagrass (Halodule wrightii) toward the shelf that create a distinct productive environment.